2019
DOI: 10.1002/jctb.5979
|View full text |Cite
|
Sign up to set email alerts
|

The conversion of glycerol to methyl lactate catalyzed by tin‐exchanged montmorillonite‐supported gold catalysts

Abstract: BACKGROUND Glycerol is a versatile platform compound to produce valuable chemicals. One‐pot direct conversion of glycerol into methyl lactate with methanol as solvent is very attractive, because it can reduce intermediate steps and avoid the separation of glycerol/methanol mixtures. RESULTS A series of tin (Sn)‐exchanged montmorillonite(M)‐supported Au catalysts were prepared by a combination of ion exchange and colloidal deposition methods, and designed as bifunctional catalysts containing gold (Au) and solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Indeed, a facile substrate channeling between the two active sites could effectively drive the reaction to the desired methyl lactate. The synthesis of such bifunctional catalysts was attempted before (using mostly intricate multi-step preparation procedures), 11,31,33,65,66 but the resulting material showed impaired catalytic performance, mostly due to the difficulty to stabilize both the Au and the Sn species in their most active forms. Here, the aerosol-assisted sol-gel synthesis was exploited to synthesize bifunctional catalysts in one step ( plus calcination).…”
Section: Bifunctional Au(x)snsio 2 Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a facile substrate channeling between the two active sites could effectively drive the reaction to the desired methyl lactate. The synthesis of such bifunctional catalysts was attempted before (using mostly intricate multi-step preparation procedures), 11,31,33,65,66 but the resulting material showed impaired catalytic performance, mostly due to the difficulty to stabilize both the Au and the Sn species in their most active forms. Here, the aerosol-assisted sol-gel synthesis was exploited to synthesize bifunctional catalysts in one step ( plus calcination).…”
Section: Bifunctional Au(x)snsio 2 Catalystsmentioning
confidence: 99%
“…Yet only a few research groups have addressed this possibility. 9,11,[31][32][33] Pescarmona et al demonstrated that a mechanical mixture of Au/CuO and Sn-MCM-41-XS could reach a 95% glycerol conversion with a ML yield up to 62% in 10.5 h. 11 Similarly, Zhou et al worked with Au/CuO and Snβ zeolites to obtain similar resultsglycerol conversion of 86% and ML yield of 60%. 33 Moving further, Tang et al emphasized that the selectivity of the first step of the cascade reaction should be targeted to increase the overall yields and focused on the improvement of the noble metal catalyst.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hence, a series of Sn-exchanged montmorillonite (Mt)-supported Au catalysts were investigated, among them, Au/Sn(20)-Mt was the best for the one-pot conversion of glycerol to methyl lactate. 61 The coexistence of small Au particles and abundant acid sites on the catalyst surface should contribute to the good performance. In the system Au-based catalyst for conversion of glycerol into lactic acid, the high cost and limited availability urgently needed for improvement.…”
Section: Au-based Catalystsmentioning
confidence: 99%
“…Moreover, Sn ion‐exchanged Mt was demonstrated to display outstanding activity and stability in the conversion of glucose to methyl lactate using methanol as a solvent. Hence, a series of Sn‐exchanged montmorillonite (Mt)‐supported Au catalysts were investigated, among them, Au/Sn(20)–Mt was the best for the one‐pot conversion of glycerol to methyl lactate 61 . The coexistence of small Au particles and abundant acid sites on the catalyst surface should contribute to the good performance.…”
Section: Heterogeneous Catalytic Systemmentioning
confidence: 99%